Dietary exposure to polychlorinated biphenyls and risk of heart failure – A population-based prospective cohort study. (May 2019) - Åkesson, Agneta; Donat-Vargas, Carolina; Berglund, Marika; Glynn, Anders; Wolk, Alicja; Kippler, Maria
Abstract: Background: Beneficial effects of fish consumption on heart failure (HF) may be modified by contaminants in fish. Polychlorinated biphenyls (PCBs) are of particular concern as they have been associated with well-established risk factors of HF, but current data are limited. Objectives: We aimed to assess the association between dietary PCB exposure and risk of HF, accounting for dietary intake of long-chain omega-3 fish fatty acids. Design: We used the prospective population-based research structure SIMPLER (previously the Swedish Mammography Cohort and Cohort of Swedish Men) comprising 32, 952 women and 36, 546 men, free from cancer, cardiovascular disease and diabetes at baseline in 1997. Validated estimates of dietary PCBs and long-chain omega-3 fish fatty acids [eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA)] were obtained via a food frequency questionnaire at baseline. Incident cases of HF were ascertained through register linkage. Results: During an average of 12 years of follow-up, we ascertained 2736 and 3128 incident cases of HF in women and men, respectively. In multivariable-adjusted models, mutually adjusted for PCBs and EPA-DHA, the relative risk (RR) for dietary PCB exposure was 1.48 (95% CI 1.12–1.96) in women and 1.42 (95% CI 1.08–1.86) in men, comparing extreme quintiles. Corresponding RRs for EPA-DHA intake were 0.71 (95% CI 0.54–0.93) and 0.82 (95% CI 0.63–1.07), respectively. Conclusions: Dietary exposure to PCBs was associated with an increased risk of HF in both women and men. EPA-DHA intake was associated with a lower risk of HF in women, with a similar tendency in men. Highlights: We explored the link of dietary PCB and EPA-DHA and heart failure in men and women. After mutual adjustment, PCB was associated with increased heart failure risk. Simultaneously, EPA-DHA intake was associated with decreased risk in women.